Clinical Presentation of Thyroglossal Cyst and its Management Study of Two Hundred Cases - Ghosh, Subrata; Chowdhury, Milon Kumar; Iqbal, Ashik; Hussain, Monowar; Siddique, Belayat Hussain (TAJ: Journal of Teachers Association, 2018)
Objectives – To find out clinical presentation, management & Complication of surgery of Thyroglossal cyst. Methods – It was a cross sectional study done in the Department of Otolaryngology and Head-Neck Surgery, BSMMU, DMCH & RMCH, from January 2009 to June 2015. 200 Patients undergoing Sistrunk’s operation for cytologically proven Thyroglossal cyst were included in this study. Patients were reviewed after sugary and any complication that occurred were recorded. Results – Within 200 patients, most (34%) were in 1st decade, mean age19.17 years, male-female ratio 1.2 : 1, in 92.5% cases cyst in midline, Complication of surgical management in 8.5% cases and recurrence is 1.5% cases after Sistrunk’s operation. Conclusions – Thyroglossal cysts commonly present as midline neck swelling within 2nd decade of life and can be successfully treated with Sistrunk’s operation with minimal recurrence. TAJ 2012; 25: 26-29